2016
DOI: 10.1016/j.humimm.2016.07.231
|View full text |Cite
|
Sign up to set email alerts
|

HLA-F coding and regulatory segments variability determined by massively parallel sequencing procedures in a Brazilian population sample

Abstract: Human Leucocyte Antigen F (HLA-F) is a non-classical HLA class I gene distinguished from its classical counterparts by low allelic polymorphism and distinctive expression patterns. Its exact function remains unknown. It is believed that HLA-F has tolerogenic and immune modulatory properties. Currently, there is little information regarding the HLA-F allelic variation among human populations and the available studies have evaluated only a fraction of the HLA-F gene segment and/or have searched for known alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 88 publications
(129 reference statements)
4
48
1
1
Order By: Relevance
“…Therefore, the description of new alleles needs to be confirmed using other gold‐standard techniques. Here, we present validation of nine novel HLA‐F alleles described by Lima et al…”
Section: Description Of Nine New Validated Alleles For Hla‐fmentioning
confidence: 79%
See 2 more Smart Citations
“…Therefore, the description of new alleles needs to be confirmed using other gold‐standard techniques. Here, we present validation of nine novel HLA‐F alleles described by Lima et al…”
Section: Description Of Nine New Validated Alleles For Hla‐fmentioning
confidence: 79%
“…The first primer sequences were GTGGCTCTCAAGGGCTCAG and GCAACAACCAAAGCATCGTA, from position −266 to 3249 according to the IPD‐IMGT/HLA Database, generating a 3515‐pb‐long amplicon. The second PCR was performed with primers described in Reference (GGAGAGAACACTCAGGTGGC and ATGGGCTGGGTGTTTAGTGG) from position −1942 to 4297 generating a 6239‐pb‐long amplicon. PCR fragments were sequenced using an NGS platform (MiSeq; Illumina, Eindhoven, The Netherlands).…”
Section: Description Of Nine New Validated Alleles For Hla‐fmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, other studies were unable to detect HLA-F transcripts in T cell lines but instead reported expression of HLA-F protein only in B cells and tissues containing B cells, such as tonsils and fetal liver (198). It is highly conserved, with 22 reported alleles encoding for four functional variants (199), suggesting a critical role in the immune response depicted by its expression on activated T-cells (200). HLA-F is expressed on monocytes and macrophages, as well on activated CD4 + T-cells as an open conformation that does not require β2M or peptide-binding (194, 197, 200).…”
Section: Hla-f Preferentially Interacts With Kir3ds1 To Elicit An Antmentioning
confidence: 99%
“…Here we present a long‐range PCR sequencing technique for genotyping HLA‐G using the Ion Torrent platform. Castelli et al have previously published an NGS method for the MiSeq platform to sequence the HLA‐G , HLA‐E , and HLA‐F genes . Apart from the fact that the sequencing platform differs between the two methods, we have also used different library preparation methods.…”
Section: Discussionmentioning
confidence: 99%